065 VO2max/kg is unreliable as an indicator of cardiac function in obese patients. (22nd September 2015) - Lewis, Nigel; Barker, Diane; O'Kane, Mary; Sharp, Lisa; Clement, Richard; Pollard, Stephen; Tan, Lip-Bun
Abstract : Background: Oxygen consumption has been conventionally normalised for different body sizes by dividing it with body weight. For instance, peak O2 consumption (VO2max) of ≤14 ml/kg/min has been widely accepted as being indicative of poor cardiac function warranting consideration for transplantation ( J Heart Lung Transplant 2006;25 :1024). However, how well division of VO2max by body weight adjusts for size in obese patients is unclear. Methods: Employing the normal ranges of VO2max of a representative British female population (n=140, age 47.5±1.2(SEM) years, BMI 25.45±0.33) as controls, we studied morbidly obese British female subjects and measured their physical and cardiac functional reserve during weight-bearing treadmill exercise testing with respiratory gas analyses and rebreathing method of non-invasively measuring cardiac outputs during peak exercise. Results: Morbidly obese women were screened and 20 (age 44.4±11.9 (SD) years, BMI 51.9±9.4) managed to exercise to acceptable cardiopulmonary limits (peak RER=1.03±0.11), and achieved VO2max of 14.4±2.2 mls/kg/min which was significantly lower than controls (27.5±5.9 mls/kg/min, p<0.001). As shown in Abstract 65 Figure 1, all subjects had VO2max of ≤18 mls/kg/min. Eight were below the transplant cutoff value of 14 mls/kg/min. However, the uncorrected VO2max (1997±368 mls/min) were within normal ranges (1828±350 mls/min, p>0.1). The peak cardiac power output (CPOmax, 5.0±1.0 W) was clearly not below normal (4.2±0.7 W, Abstract 65 Figure 2 ). Of the eight patients with VO2max/kg below the transplant cutoff, all had above average normal CPOmax. Conclusion: The conventionally measured VO2max/kg suggests that obese patients have very poor cardiac function, but this contradicted with evidence from directly measured cardiac reserve. The use of VO2max corrected with body weight for transplant assessment can be misleading and needs reappraisal.